Association between walking speed and cognitive domain functions in Chinese suburban-dwelling older adults - Wang, Hong; Zhang, Hui; Chen, Yaoxin; Cai, Ming; Guo, Cailian; Chen, Peijie (Frontiers in Aging Neuroscience, 2022)
Objective: To examine the relationship between walking speed, cognitive impairment, and cognitive domain functions in older men and women living in a Chinese suburban community. Methods: 625 elderly (72.54±5.80 years old) men (n= 258) and women (n= 367) from Chongming district of Shanghai participated in this study. All participants had mini-mental state examination (MMSE), 4-meter walking test, medical history questionnaire and physical examination. They were grouped according to walking speed (>0.8m/s vs ≤0.8m/s) with the stratification of sex. Odds ratio (OR) and the 95% confidence interval (CI) were assessed using Chi-square test and logistic regression analysis. Results: 11.6% men and 14.2% women, respectively, had slow walking speed. After adjusting for age, BMI, education level, spouse, faller, GDS score, heart disease, stroke, arthritis, and low back pain, walking speed was negatively related to cognitive impairment in men (odds ratio 0.11 [95% CI 0.01, 0.94]; P = 0.043). In addition, the relationship between walking speed and impaired orientation was significant in both men (Odds ratio 0.003 [95% CI 0.001, 0.05]; P ＜0.001) and women (odds ratio 0.15 [95% CI 0.03, 0.75]; P=0.021). Conclusion: The relationship between walking speed and cognitive impairment was only significant in men, but the association with impaired orientation was found in both men and women. Assessing the walking speed of the elderly is beneficial, which may help with early detection and early therapeutic prevention of cognitive impairment.